The Practice and Importance of Chestnut Cultivation in Azerbaijan in the Face of Blight, Cryphonectria parasitica (Murrill) Barr - Wall, Jeffrey Robert; Aghayeva, Dilzara N. (Ethnobotany Research and Applications, 2014)
The arrival and spread of chestnut blight, caused by the fungus Cryphonectria parasitica (Murrill) Barr, in Caucasian Azerbaijan has compromised the livelihoods of chestnut farmers and is causing rapid genetic erosion in the center of diversity for the European chestnut, Castanea sativa Mill. In Azerbaijan, blight was first reported in 2008 and is currently present in all chestnut-growing regions. Fortunately, there is a demonstrated biological control technique which may be applied in the context of Europe and Eurasia. This presents an opportunity to simultaneously achieve environmental and genetic resource conservation goals while reinforcing the livelihoods and maintenance of diversity of the nation’s chestnut growers. However, national institutions primarily recognize the economic and genetic importance of certain elite crops, particularly those which were prominent production goods during the Soviet period. The present work was undertaken to characterize the socio-economic role of chestnut production and use in the communities where this crop is grown and sold. We investigate the monetary role of chestnut sales in the livelihoods of growers and collectors. It is hypothesized that while continuing to be a minor production good nationally, chestnut sales in a newly entrepreneurial agricultural sector have taken on tremendous livelihood importance to specific communities. The socio-economic importance of chestnut-based income to Azerbaijan’s chestnut-growing communities is illustrated by the results of in-depth household budget interviews from 22 chestnut-growing households in two villages.